THE CORRELATION BETWEEN STUDENT MOTIVATION AND STUDENT SPEAKING SKILLS AT SMPN 1 JEUMPA ACEH BARAT DAYA - Elfiza Ola; Zuhri Efendi (Nusantara Hasana Journal, 2023)
Students' speaking skills are skills that are difficult and a challenge in themselves for students in Indonesia as foreign language users. This research aims to find out whether there is a significant relationship between student motivation and student speaking skills. This research a quantitative approach and correlation research methods which are used through statistical tests. The population in this study was 60 students’ consisting of 25 male students and 35 female students and the sample taken was 30 students consisting of 15 male students and 15 female students. In collecting research data, a questionnaire was used to collect data about motivation. students and oral tests to collect data on speaking skills. After analysis by researchers, it was found (0.427 > 0.361), which means there is a relationship between these two variables.